138k views
5 votes
Solve the system.



6x - 2y + z = -2
2x + 3y – 3z = 11
х+ 6у = 31

User LoneStar
by
6.0k points

1 Answer

4 votes
  • 6x - 2y + z = -2 .......... (i)
  • 2x + 3y – 3z = 11 ...........(ii)
  • х + 6у = 31 ..............(iii)

After Multiplying 3 with the eq. (i) we will add this to eq. (ii)


\sf 18x - 6y + 3z = - 2


\sf2x + 3y - 3z = 11

_______________________


⇒ \sf20x - 3y = 9 \: \: .........(iv)

After Multiplying 2 with the eq. (iv) we will add this to eq. (iii)


\sf \: x + 6y = 31


\sf40x - 6y = 18

_________________


\sf \: 41x = 49


⇒ \sf \: x = (49)/(41)

After putting the value of x in the eq. (iii)


\sf (49)/(41) + 6y = 31


⇒ \sf6y = 31 - (49)/(41)


\sf \: ⇒ 6y = (1271 - 49 )/(41)


⇒ \sf6y = (1222)/(41)


⇒ \sf \: y = (1222)/(41 * 6)


⇒ \sf \: y = (611)/(123)

After putting the value of x and y into eq. (i)


\sf6 * (49)/(41) - 2 * (611)/(123) + z = -2


⇒ \sf(294)/(41) - (1222)/(123) + 2 = - z


⇒ \sf (882 - 1222 + 246)/(123) = - z


⇒ \sf - (94)/(123) = - z


⇒ \sf \: z = (94)/(123)

Hence,


\bf • \: The \: value \: of \: x = (49)/(41) </strong></p><p><strong>[tex] \bf • \: The \: value \: of \: x = (49)/(41)


\bf • \: The \: value \: of \: y = (611)/(123)</strong></p><p><strong>[tex] \bf • \: The \: value \: of \: y = (611)/(123)


\bf• \: The \: value \: of \: z \: = (94)/(123)

User Bprayudha
by
6.2k points